Effect of plate-like particles on properties of poly(lactic acid)/poly(butylene adipate-co-terephthalate) blend: A comparative study between modified montmorillonite and graphene nanoplatelets. (23rd November 2015) - Girdthep, Sutinee; Komrapit, Nopparat; Molloy, Robert; Lumyong, Saisamorn; Punyodom, Winita; Worajittiphon, Patnarin
Abstract: Surface-modified montmorillonite (mMMT) and graphene nanoplatelets (GNPs), both possessing plate-like structure, were adopted as property enhancers for a blend based on poly(lactic acid) and poly(butylene adipate- co -terephthalate). Unlike mMMT, GNPs contributed to higher stretchability of the solvent-cast films compared to that of the polymer-clay composite films. Fine dispersion of GNPs throughout the polymer host promoted several improved properties of the blend. Compared to the mMMT at identical filler amount, GNPs enhanced thermal stability and water vapor barrier property while decreased light transmittance in controllable fashion by simply tuning the GNP loading content (0.1–1 phr). In contrast, the clay did not show any obvious trend of property enhancement. Thus, GNPs functioned as promising property improver for this selected blend. Finally, the polymer-graphene composite could find further application in conductive coating of metal electrodes. This paper shows the simple preparation of polymer composite films by using fillers without any complicated functionalization. The findings will also benefit further facile processing of engineering composites. Graphical abstract: